Ethnomedicinal, Phytochemical and Nutra-pharmaceutical Potentials of Indian Arrowroot (Curcuma angustifolia Roxb) - Kityania, Sibashish; Talukdar, Anupam D.; Nath, Rajat; Nath, Deepa; Choudhury, Manabendra Dutta; Nizamee, Abu Md Hassan; Patra, Jayanta Kumar (Combinatorial Chemistry & High Throughput Screening, 2023)
Indian Arrowroot (Curcuma angustifolia Roxb) belonging to the Zingiberaceae family is widely distributed in India and some parts of Nepal, Thailand, Bangladesh and Pakistan. It is traditionally used as medicine for treating various diseases and also used as food. Few data are available about its application in pharmacology and therapeutics. Literature search for related contents, keywords such as “Curcuma angustifolia Roxb”, “traditional food”, “ethnomedicine”, “pharmacology”, “phytochemicals”, “pharmacological activities” were used in search engines including PubMed, Google Scholar, Scopus, ScienceDirect, and Semantic Scholar. Secondary metabolites found in Indian Arrowroot include essential oils, alkaloids, flavonoids, terpenoids, phytosterols, terpenes, phenols, and others. Pharmacological activities such as antioxidant, antiinflammatory, anti-proliferative, anti-ulcerogenic, hepatoprotective, and anti-cancerous activities have been shown by Indian Arrowroot (Curcuma angustifolia Roxb). The presence of nutritional value and pharmaceutical potential gained demand in the various food production industries and pharmacology research. It may play a vital role in future studies of Curcuma angustifolia Roxb as ethnomedicine and further exploitation in pharmacological studies.
Keywords: food